Pemanfaatan media pembelajaran interaktif dalam meningkatkan motivasi belajar siswa Sekolah Dasar - Mardhiyah, Ifatul (Maliki Interdisciplinary Journal, 2025)
This study aims to describe the utilization of interactive learning media in enhancing elementary students’ learning motivation. Interactive media is believed to create a more enjoyable and participatory learning atmosphere, aligned with the characteristics of today’s digital generation. This study employed a descriptive qualitative approach with subjects from third and fourth-grade students at an Islamic elementary school in Malang Regency. Data were collected through observation, interviews, and documentation. The findings revealed that the use of interactive media, such as technology-based educational games and interactive presentation applications, significantly increased students’ enthusiasm, focus, and engagement in the learning process. Students felt more motivated since the learning activities were not monotonous and provided opportunities for active participation. In conclusion, interactive learning media play a crucial role in fostering students’ learning motivation, and teachers are encouraged to continuously integrate technology into their teaching practices.